Odpowiedzi

2010-02-09T15:05:33+01:00
-2x+y=-8
4x-3y=2

y=-8+2x
4x-3(-8+2x)=2

y=-8+2x
4x+24-6x=2

y=-8+2x
-2x=2-24

y=-8+2x
-2x=-22 / :2

y=-8+2x
x=11

y=-8+2*11
x=11

y=-8+22
x=11

y=14
x=11
Najlepsza Odpowiedź!
2010-02-09T15:06:33+01:00
{-2x+y=-8 /*2
{4x-3y=2

{-4x+2y=-16
{4x-3y=2
_____________
-y=-14
{y=14
{4x-3y=2

{y=14
{4x-42=2

{y=14
{4x=44

{y=14
{x=11
2010-02-09T15:07:43+01:00
-2x+y=-8//*3
4x-3y=2

-6x+3y=-24
4x-3y=2
---------------
-6x+4x=-24+2
-2x=-22//:(-2)
x=11

-2x+y=-8
-2*11+y=-8
-22+y=-8
y=-8+22
y=14


x=11
y=14